Optimizing fisheries assets and levies to enhance regional revenue in East Kalimantan - Oktawati, Nurul Ovia; Gunawan, Bambang Indratno; Ningsih, Etik Sulistiowati; Darmasetiadi, Doni; Kusumaningrum, Indrati (Agriekonomika, 2026)
The fisheries sector plays a strategic role in supporting regional fiscal independence in coastal provinces such as East Kalimantan; however, a persistent gap remains between its economic potential and realized Regional Original Revenue (PAD). Using a descriptive-quantitative approach combined with asset-based valuation and fiscal scenario analysis, this study examines the structure and performance of fisheries levies and evaluates the fiscal potential of key public fisheries assets based on primary interviews and official administrative data. The results show that fisheries levies reached IDR 1.08 billion in 2023, while the estimated fiscal potential could reach approximately IDR 4.3 billion per year, representing an increase of nearly 300 percent under integrated optimization scenarios. Hatchery facilities with an actual production capacity of about 1.2 billion fish and shrimp seedlings annually constitute the largest source of unrealized fiscal value. This study demonstrates that short-term gains can be achieved through port service optimization, auction revitalization, and hatchery asset intensification, while longer-term opportunities arise from revenue-sharing mechanisms under quota-based fisheries policies (PIT). The novelty of this research lies in its integrated analytical framework that combines levy structure analysis, public asset valuation, and strategic prioritization to assess fisheries-based fiscal autonomy at the regional level.